Proxy Notes Recognition and Eradication for Betterment of the Society - Hariharan, G; Elangovan, D (International Journal of Computer Sciences and Engineering, 2020)
The economy of the country can be calculated based on the circulation of the currency in it. Faux notes circulation is one of the major problems of the various countries .Due to the circulation of the faux note the economy of the countries will be affected drastically. So in order to remove the counterfeit notes from the circulation various methods have been proposed. But there are some drawbacks in the proposed methods. In order to increase the rate of accuracy to determine the faux note the proposed system uses the machine learning with the help of MatLab to increase the rate of accuracy to determine the faux note in the circulation.